Подход к автоматизации управления высшим учебным заведением Украины - Бондаренко, М. Ф.; Левыкин, В. М.; Евланов, М. В.; Неумывакина, О. Е. (My University, 2003)
Даються відомості про стан і шляхи вирішення проблеми автоматизації управління вищими навчальними закладами України. Визначаються головні напрямки автоматизації діяльності навчального закладу. Як приклад реалізації типового підходу до вирішення даної проблеми розглядаються основні особливості проектних рішень першої черги інформаційно-аналітичної системи «Університет». Пропонуються шляхи подальшого вдосконалення даної інформаційної системи Information on the state and ways of solving the problem of automation of management of higher educational institutions of Ukraine is given. The main directions of automation of the educational institution activity are determined. As an example of the implementation of a typical approach to solving this problem, the main features of the design solutions of the first stage of the information-analytical system "University" are considered. Proposed ways to further improve this information system
Keywords: информационно-аналитическая система «Университет»; функциональная подсистема; свойства системы; обеспечивающая часть